A fuzzy-based model for risk assessment of routes in oil transportation - Gul, M.; Guneri, A. F.; Nasirli, S. Miralp (SPRINGER, 2019)
The transportation of oil is the final step that the oil is taken before it is distributed to consumer. Road transport is a type of oil transportation methods, and transfers between facilities of primary and secondary bases are carried out by tanker trucks. A particular advantage of tanker trucks is that they provide direct travel from the source to the destination. However, road transport involves possible hazards for population and environment. At this point, this study presents a fuzzy-based risk assessment model for the routes in an oil transportation company. Fuzzy analytic hierarchy process, which is a commonly used multi-criteria decision-making method, is applied in weighting nine criteria related to the road characteristics. Then, risk scores for eleven different routes which the tanker trucks of the company followed are determined by using a basic multi-criteria scoring method. Results of the case study emerge that the most important criterion is narrow road. The riskiest route for the company has been determined. In order to reduce risks to an acceptable level, a number of control measures are suggested such as to assign experienced drivers for this route, provide regular training for drivers, make regular vehicle maintenance and transport large quantities at one time as possible. To demonstrate validity, a comparison is also provided between the proposed approach and Pythagorean fuzzy analytic hierarchy process-based risk scoring model. In conclusion, this study contributes to the applicability of fuzzy analytic hierarchy process to assess riskiness for routes in oil transportation.
Keywords: Fuzzy analytic hierarchy process; Oil transportation; Risk assessment; Risk scoring; Road transport routes; OCCUPATIONAL-HEALTH; DECISION; SAFETY; ROAD; AHP; ENVIRONMENT; STRATEGIES; FRAMEWORK; Environmental Sciences & Ecology